Anticancer potential and synthesis of salicylic acid and eugenol molecular hybridization: With and without linked amino acids - Warsito Warsito,, Dwika Putri Pangesti, Masruri Masruri, Sinta Murlistyarini, Christy Patricia Siregar, Wahyu Abdul Wachid (Journal of Applied Pharmaceutical Science, 2024)
This research investigates the discovery of cancer drugs through a hybrid approach involving two essential oil molecules, salicylic acid, and eugenol, with or without an amino acid linker. Developing these anticancer drugs employs computational methods, including ADMET, Lipinski rules, and in-silico docking against seven cancer receptors: MMP9, MMP2, CDK2, P53, BAK, epidermal growth factor receptor, and MRPR. The synthesis of nonlinker hybrid molecules involves esterification reactions with DCC and DMAP as catalysts, while hybrid molecules with an alanine amino acid linker undergo a two-stage process: amidation with DCC catalyst and esterification using DCC/ DMAP catalyst. Characterization of the synthesis products is performed using thin-layer chromatography, FTIR, and LCMS methods. ADMET and Lipinski rule analysis of nonlinker and alanine linker hybrid molecules indicates that they meet the criteria for drug candidates. Additionally, docking results show that nonlinker hybrid molecules are active against the BAK receptor (PDB ID: 6UXM), making them suitable as pro-apoptotic agents. On the other hand, alanine linker hybrid molecules are active against the MMP9 enzyme (PDB ID: 4H1Q), responsible for cancer migration, and also active against the pro-apoptosis BAK receptor (PDB ID: 6UXM). The analysis of nonlinker hybrid molecule synthesis reveals a yield of 59.85%. Meanwhile, the analysis of hybrid molecules with an alanine linker shows a yield of 93.89%.
Keywords: Linked, hybridization, eugenol, salicylic acid, amino acid, anticancer